Mergers, acquisitions, and corporate restructurings - Gaughan, Patrick A. (Delhi Wiley, 2014)
Modern restructuring techniques for a global business landscape. Mergers, Acquisitions, and Corporate Restructurings, Fifth Edition carefully analyzes the strategies and motives that inspire M & As, the laws and rules that govern the field, as well as the offensive and defensive techniques of hostile acquisitions.: Incorporates updated research, graphs, and case studies on the private equity market, ethics, legal frameworks, and corporate governance; Expanded and updated chapters on corporate governance, joint ventures and strategic alliances and valuation; Expanded global treatment of the field.
MERGERS, ACQUISITIONS, AND CORPORATE RESTRUCTURINGS, FIFTH EDITION; CONTENTS; CASE STUDIES; PREFACE; PART I: BACKGROUND; CHAPTER 1: INTRODUCTION; CHAPTER 2: HISTORY OF MERGERS; CHAPTER 3: LEGAL FRAMEWORK; CHAPTER 4: MERGER STRATEGY; PART II: HOSTILE TAKEOVERS; CHAPTER 5: ANTITAKEOVER MEASURES; CHAPTER 6: TAKEOVER TACTICS; PART III: GOING-PRIVATE TRANSACTIONS AND LEVERAGED BUYOUTS; CHAPTER 7: LEVERAGED BUYOUTS; CHAPTER 8: TOPICS IN GOING-PRIVATE TRANSACTIONS; CHAPTER 9: EMPLOYEE STOCK OWNERSHIP PLANS; PART IV: CORPORATE RESTRUCTURING; CHAPTER 10: CORPORATE RESTRUCTURING.
Keywords: Consolidation and merger of corporations; Corporate reorganizations